Motivational approach to lifestyle modification intervention on cardiometabolic risk profiles among obese adults: a randomized controlled trial - Shahadan, Siti Zuhaidah (2018)
Background: Lifestyle modification intervention (LMI) is effective in promoting cardiometabolic risk (CMR) reduction. However, the current standard LMI for obese adults in Malaysia has only a periodic review. Hence, this study aims to determine the effect of LMI with a motivational approach on CMR profiles among obese adults. Methods: This is a randomized controlled trial with an intervention group who received a 6-month LMI with a motivational approach and a control group, who received a 6-month standard LMI. The independent sample and paired t-test are used to determine the significant differences in the CMR profile between the intervention and control group after six months and between the pre- and post-intervention assessment, respectively. Results: The findings showed that the obese adults in the intervention group (n=40) had a positive outcomes to the CMR profile through a significant reduction in the body mass index (p=0.002) and a significant rise in high-density lipoprotein level (p=0.021) after six months. Additionally, the intervention group also achieved a reduction in the low-density lipoprotein and high-sensitivity C-reactive protein level after six months. Contrariwise, the control group (n=39) had an unexpected significant rise in fasting blood glucose level (p=0.012) and the low-density lipoprotein and high-sensitivity C-reactive protein level was increased after six months. Both the intervention and control group also had a significant reduction in the waist circumference measurement after six months (p<0.05). Conclusions: The LMI with the motivational approach is clinically more effective than the standard treatment to improve the CMR profile of obese adults after six months. Consequently, larger trials with specific sub-groups of obese adults, such as those with pre-diabetes or pre-hypertension, are warranted.